Taxonomy and phylogeny of Phellinidium (Hymenochaetales, Basidiomycota): A redefinition and the segregation of Coniferiporia gen. nov. for forest pathogens - Zhou, Li-Wei; Vlasák, Josef; Dai, Yu-Cheng (Fungal biology, 2016)
Phellinidium, including 13 accepted polypore species mostly with resupinate basidiocarps, is one of the most aggressive forest pathogenic genera. This genus is characterized by the combination of a monomitic hyphal structure, abundant hyphoid setae in the context and trama, and hyaline and thin-walled basidiospores. To explore the relationships among the species of Phellinidium, especially those between forest pathogens and saprophytes, we examined 29 specimens representing all 13 previously known species from Asia, Europe and America from morphological and phylogenetic perspectives. A new genus, Coniferiporia, was found to segregate from Phellinidium for three aggressive forest pathogens, and three new combinations, viz. Coniferiporia qilianensis (the generic type), Coniferiporia weirii and Coniferiporia sulphurascens, were proposed. Phellinidium cryptocystidiatum was treated as a synonym of C. sulphurascens. The circumscription of Phellinidium was delimited to accommodate Phellinidium asiaticum, Phellinidium ferrugineofuscum (the generic type), Phellinidium fragrans and Phellinidium pouzarii. Accordingly, the concept of Phellinidium was emended to accommodate resupinate species bearing cylindrical to oblong-ellipsoid or allantoid basidiospores. No species of Phellinidium under the new circumscription has been reported to be a forest pathogen. Phellinidium noxium and Phellinidium rufitinctum were excluded from Phellinidium, while the taxonomical positions of Phellinidium aciferum, Phellinidium lamaënse, and Phellinidium orientale are still uncertain.
Keywords: DNA, Ribosomal Spacer; Sequence Analysis, DNA; Europe; Genes, rRNA; hyfy; DNA fungální; Asie; fungální RNA; Evropa; Spores, Fungal; Basidiomycota; DNA, Ribosomal; Cluster Analysis; spory hub; geny rRNA; Hyphae; fylogeneze; lesy; ribozomální DNA; DNA, Fungal; Amerika; nemoci rostlin; sekvenční analýza DNA; Asia; Americas; RNA ribozomální; Phylogeny; RNA, Fungal; RNA, Ribosomal; shluková analýza; mezerníky ribozomální DNA; Forests; Plant Diseases